O microrganismo no trabalho de Pasteur: estudos sobre a fermentação e putrefação - Rodrigues, Sabrina Páscoli (2014)
Louis Pasteur devoted himself to a wide variety of studies during his career. Surrounded by the fame of great genius and benefactor of humanity, Pasteur was linked to major controversy within the scientific community. This thesis deals with some of Pasteur's contributions to the fermentation, putrefaction and reasoning of germ theory of disease, analyzing what was the path taken by the scientist from crystallography to biological conception of disease. It also discusses the position of other scientists in the same period on these subjects. From this research, it was possible to analyze how Pasteur's research transformation took place and what were the arguments and evidence found by him to defend his point of view, that the microorganism was the protagonist of several reactions and transformations of substances and also had influence on other living beings. This work aims to contribute to current studies on Pasteur and his work, which seek to rebuild its image as a great researcher of his time, involved in a large network of scholars, which enabled the development of his investigations